2006 IEEE Intelligent Transportation Systems Conference 2006
DOI: 10.1109/itsc.2006.1706748
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Path Travel-Time Reliability

Abstract: The estimation of path or trip travel-time reliability is critical to any Advanced Traveler Information System. The state-of-practice procedures for estimating path travel-time reliability assumes that travel times follow a normal distribution and requires a measure of trip travel-time variance. The study analyzes AVI data from San Antonio and demonstrates through goodness-of-fit tests that the assumption of normality is, from a theoretical standpoint, inconsistent with field travel-time observations and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 3 publications
1
39
0
Order By: Relevance
“…The evaluation is done using dataset from a taxis fleet in San Francisco, CA, as a part of The Mobile Millennium Project. To model the correlation and dependency in transport networks, Rakha et al (2006) have tried to estimate the variance of freeway route travel time by modeling correlation between segment travel time variances. Geroliminis and Skabardonis (2006) also estimated the variance of urban route travel time by assuming linear correlations between successive links travel times.…”
Section: Travel Time Estimation Literature Reviewmentioning
confidence: 99%
“…The evaluation is done using dataset from a taxis fleet in San Francisco, CA, as a part of The Mobile Millennium Project. To model the correlation and dependency in transport networks, Rakha et al (2006) have tried to estimate the variance of freeway route travel time by modeling correlation between segment travel time variances. Geroliminis and Skabardonis (2006) also estimated the variance of urban route travel time by assuming linear correlations between successive links travel times.…”
Section: Travel Time Estimation Literature Reviewmentioning
confidence: 99%
“…This assumption was supported by Rakha et al [36], which demonstrated that the normality assumption may be sufficient from a practical standpoint given its computational simplicity. Equation (19) can be calculated as follows:…”
Section: Stochastic Link Travel Time and Stochastic Path Travelmentioning
confidence: 89%
“…Rakha et al [36] presented extensive evidence of a significant correlation between travel times of two adjacent links in the network. Although they analyzed travel time variability over vehicles, this evidence may support travel time variability over days.…”
Section: Simplificationmentioning
confidence: 99%
“…From the aspect of microscopic approach, models of vehicle dynamics are preferred in the paper. Alternative truck lane management strategies are evaluated in [19]. The efficiency of this method is presented by different scenarios, which show that using these methods travel time, energy and the emission of the vehicle can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of this method is presented by different scenarios, which show that using these methods travel time, energy and the emission of the vehicle can be reduced. [19,20] present modeling methods for the design of route guidance strategies and the reliable estimation of travel time. The preliminary results of the research are also published in [14,15].…”
Section: Introductionmentioning
confidence: 99%